DEVELOPMENT OF DIGITAL LITERACY OF STUDENTS IN THE TRAINING SYSTEM - Nilufar Xalikova Mirkadirovna (Galaxy International Interdisciplinary Research Journal, 2023)
This article shows the theoretical basis and scientific analysis of the development of digital competence of pedagogues by applying modern methods of teaching with the help of digital educational technologies.